Analisis Yuridis dalam Pemberian Hak serta Ganti Rugi terhadap Korban Tragedi Kanjuruhan - Nurul A’fiah; Imam Ridar Ramadhan; Shahnaz Andjelina; Beril Nugraha; Rachmatullah Mahesa; Ahmad Maulana Arifin (Terang : Jurnal Kajian Ilmu Sosial, Politik dan Hukum, 2024)
Human rights violations are actions that violate humanitarian principles, which are principally carried out by individuals, state institutions, or other institutions, which aim to deprive other individuals of their human rights without juridical pretexts and convincing rational evidence. Human rights violations that currently occur often have a high complexity. One of them is the human rights violations that occurred in the tragedy at Kanjuruhan Stadium, Malang on October 1, 2022. The impacts of the tragedy experienced by victims and their families include physical, emotional and financial. After the Kanjuruhan incident, it is necessary to limit the rights and responsibilities between parties who have a role in organizing football matches. So, for this reason, structured steps are needed to restore the rights of victims that should be given. The method used in this research is the normative juridical method by making secondary data as research material obtained from books, similar works and research, as well as draft laws. This research highlights the importance of implementing compensation and restitution mechanisms as an effort to restore victims' rights, in accordance with applicable law. Through in-depth analysis of relevant legal regulations and related cases, this research provides insight into the efforts that have been made by the government and related institutions in providing compensation and restitution to victims.